Place identity and urban attachment of international students - Srpski; Srpski, Srpski (Sociološki pregled, 2024)
The hypothesis of this totally novel research in Serbia is that the way in which place may influence the identity of international students integrates a part of their individual identities, but also influences the variability of identities deriving from various contextual factors of the student migration’s origin. Cities can be observed through their respective role in shaping and transforming the international students’ identity. The goal is to examine emotional and functional attachment of international students to the city in which they study, in comparison to these two components of attachment to the place of their origin. The testing of theoretical standpoints is based on qualitative research through focus-group interviews with three designed groups of respondents and the results of this testing will be additionally validated later in triangulation with questionnaires and interviews as complementing research techniques and approaches.